Babylonian theater (Its history, models and properties) a historical comparative study: محمد صبري صالح (Al-Academy, 2016)
The building of the Babylonian theater is considered as one of the distinctive buildings where its foundations have remained steadfast in the face of geographical changes, social's erosion and groundwater that threatened almost all traces of Babylon despite the destruction of the outer structure of the building. The general directorate of antiques performed prospection for those foundations (the ground map), and then the building was completed by new bricks over the original scheme. It became clear when examining the building; its components and foundations, that the building is unique in comparison with the old buildings of the world throughout Iraq. There are similar buildings in other places like Jordan and North Africa such as Leptis Magna's theater and Sabratha's theater which were built by the Greeks in Libya. A confusion has been emerged about the real builder of the theater where there is no document dated whether the building attributed to a company or a person. To manage this problem, the researcher reviewed the historical documents that could refer to that case. Moreover, he conducted an architectural and sociological comparison between Babylonian theater and the Greek and Roman theaters which were known and built in synchronized intervals with the creation of the Babylonian theater in order to know the differences and similarities between them.The researcher used descriptive and comparative method in the analysis, based on historical documents in order to reach logical conclusions that may dispel those doubts and solve the problem.The most important findings were the existence of the Babylonian theater building before entering Alexander the Great to the city of Babylon, the uniqueness and specificity of this building and the lack of full similarity between Babylonian theater and the Greek and Roman theaters